Efektivitas Audiovisual dan Booklet sebagai Media Edukasi untuk Meningkatkan Perilaku Skrining IVA - Silalahi, Veronica; Hakimi, Mohammad; Lismidiati, Wiwin (Media Kesehatan Masyarakat Indonesia, 2018)
Cervical cancer is the caused of high maternal mortality. Prevention of cervical cancer done by screening Visual Inspection with Acetic Acid (IVA). The objective of this study to analyzed the effectiveness of health education applying health belief model using audiovisual and booklet on female behavior for IVA examination in the work area of Pacarkeling Public Health Center. The research method used Quasi Experimental with Design Non- Equivalent Control Group Design. Research subjects were women aged 30-50 years who have never done previous IVA examination. Sample selection using cluster sampling technique with sample of 79 respondents for each group of intervention and control group. Health education using audiovisual and booklet. Data analyzed using wilcoxon test, chi-square, mann-whitney, and linear regression. Health education using audiovisual and booklet effective in improving the behavior of respondents for IVA screening. Increased of knowledge, attitudes, health belief of the intervention group is greater than control group. The behavior of women in IVA screening for intervention group was greater than control group after intervention. External variables such as age, education, occupation, income, previous information have an effect on behavior improvement. Health education is effective in improving women behavior for IVA screening